PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA GURU PADA SD KARTIKA 1-11 PADANG - Nazarudin Aziz; Septianto Dwi Putra (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
This study aims to determine: 1. To determine the effect of leadership style on teacher performance at SD Katika 1-11 Padang. 2. To determine the effect of motivation on teacher performance at SD Kartika 1-11 Padang. The method used in this study is a quantitative research method with a descriptive approach to the population. of 40 teachers. The data collection technique used a questionnaire with the sampling technique was total sampling while the data source was primary data. The data analysis technique used multiple linear regression using the SPSS version 26.00 program. The hypothesis was tested using t test at = 0.05. The data analysis techniques used were validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, hypothesis T test. The results of this study indicate that: 1. The results showed that leadership style had no significant effect on teacher performance at SD Kartika 1-11 Padang 2. The results showed that motivation had a significant effect on teacher performance at SD Kartika 1-11 Padang